The Development of Powtoon-Based Mathematics Learning Media Oriented Toward Learning Outcomes on Cartesian Coordinate Material for Grade VIII Students Junior High School - Khairi, Nashrul; Turmuzi, Muhammad; Lu’luilmaknun, Ulfa; Hikmah, Nurul (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
Mathematics is an essential subject, but some students face difficulties in learning due to the lack of engaging and innovative learning resources. However, using PowToon-based learning media in videos can be an effective alternative for distance education. This study aimed to develop PowToon-based mathematics learning media that would be valid, practical, and effective for the eighth-grade Cartesian coordinate material at SMP Negeri 13 Mataram, using the 4D research method (Define, Design, Development, Dissemination). The research resulted in an MP4 video about Cartesian Coordinate material that received a validity score of 0.82, which was considered highly valid by four validators. The product is also considered practical, with an 84.6% practicality score based on the responses of 24 students who used it for the Cartesian coordinate material. The media has proven highly effective, with a student completion rate of 83.33% during the test trial. Furthermore, the learning media is disseminated through YouTube for easy student access. Thus, PowToon-based learning media can be considered valid, practical, and effective for mathematics education.